A novel highly electrically conductive composite resin for stereolithography. (June 2019) - Scordo, Giorgio; Bertana, Valentina; Scaltrito, Luciano; Ferrero, Sergio; Cocuzza, Matteo; Marasso, Simone L.; Romano, Stefano; Sesana, Raffaella; Catania, Felice; Pirri, Candido F.
Abstract: The use of 3D printing for scientific and industrial applications is rapidly increasing and, simultaneously, is growing the interest toward printable smart materials. It is known that using a conductive filler, e.g. nanoparticles, metal powders or composite polymers, it is possible to produce a more electrically conductive printable material. The PEDOT:PSS polymer has been used extensively, from bioelectronics to energy storage devices, for its conductivity and biocompatibility. In this work, a highly electrically conductive resin for Stereolithography was developed using a dispersion of PEDOT particles, extracted from Clevios™ PH1000 through a simple separation process, in a PEGDA matrix. The resin composition was optimized in terms of photoinitiator, surfactant and filler concentration. Furthermore, optimal printing parameters were determined for this composite resin, obtaining a printed object with appreciable electrical conductivity (0.05 S cm −1 ) and mechanical properties (Young modulus 21 MPa).